MiR‐200c enhances radiosensitivity of human breast cancer cells. Issue 3 (22nd January 2013) - Lin, Jing; Liu, Cong; Gao, Fu; Mitchel, R.E.J.; Zhao, Luqian; Yang, Yanyong; Lei, Jixiao; Cai, Jianming
Abstract Due to the intrinsic resistance of many tumors to radiotherapy, current methods to improve the survival of cancer patients largely depend on increasing tumor radiosensitivity. It is well‐known that miR‐200c inhibits epithelial–mesenchymal transition (EMT), and enhances cancer cell chemosensitivity. We sought to clarify the effects of miR‐200c on the radiosensitization of human breast cancer cells. In this study, we found that low levels of miR‐200c expression correlated with radiotolerance in breast cancer cells. miR‐200c overexpression could increase radiosensitivity in breast cancer cells by inhibiting cell proliferation, and by increasing apoptosis and DNA double‐strand breaks. Additionally, we found that miR‐200c directly targeted TANK‐binding kinase 1 (TBK1). However, overexpression of TBK1 partially rescued miR‐200c mediated apoptosis induced by ionizing radiation. In summary, miR‐200c can be a potential target for enhancing the effect of radiation treatment on breast cancer cells. J. Cell. Biochem. 114: 606–615, 2013. © 2012 Wiley Periodicals, Inc.